Estilo de liderazgo directivo y clima organizacional en una institución educativa del distrito de Ventanilla - región Callao - Campos Livaque, Lily Roxana (2012)
The purpose of this study was to establish the relationship between directive leadership style and organizational climate in a school in the district of Ventanilla, Callao Region, the design of this investigation was correlational. The participants were 50 teachers,30 parents and 20 students. The instruments constructed and employed are the scale of directive leadership (Ruiz, 2009) which measured 3 dimensions and the organizational climate (Berrocal, 2007) which also measured 3 dimensions. Both showed validity and statistical reliability. The results were obtained through the chi square test. Concluding the investigation with the existence of relationship between directive leadership and organizational climate, creating democratic.